Charge-Collection Efficiency in Back-Illuminated Charge-Coupled Devices - Fernández Moroni, Guillermo (2021)
Low-noise fully depleted charge-coupled devices have been identified as a unique tool for dark-matter searches, low-energy neutrino physics, and x-ray detection. The charge-collection efficiency (CCE) for these detectors is a critical performance parameter for current and future experiments. We present a technique to characterize the CCE in back-illuminated CCDs based on soft x rays. This technique is used to study two different detector designs. The results demonstrate the importance of the backside processing for the detection of charge packages near threshold, showing that a recombination layer of a few microns significantly distorts the low-energy spectrum. The studies demonstrate that the region of partial charge collection can be reduced to a thickness of less than 1μm with adequate backside processing.